CORRESPONDENCE BETWEEN CADASTRAL-REGISTER SYSTEM OF UKRAINE AND STANDARDS OF SIMILAR EU SYSTEMS - Kozlova, Tatiana; Burdilna, Yana; Pismenna, Maria (Proceedings of National Aviation University (archive), 2014)
The experience and main trends of development, modernization and standardization of cadastral-register systems in Europe are presented. Current practice and EU requirements for creation of cadastral-register systems are analyzed. Correspondence between cadastral-register system of Ukraine and standards of similar EU systems is defined. Such basic criteria as efficiency, accuracy and reliability, customer orientation, service efficiency, the minimum cost are determined